Students’ Perceptions of English Blended Learning During the New Normal Era - Arifi Dwi Fadila; Faurina Anastasia (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
This study aims to determine students’ perceptions of the blended learning model for learning English in the new normal era. Using a quantitative research method design, the data were collected from students in classes XI, IPA, and IPS using simple random sampling. 56 students were selected as research samples using a simple random sampling technique. In collecting the data, the researcher distributed a questionnaire to students. The researcher used descriptive statistics to analyze the data and made it easier by using the SPSS 25 program. The results showed that students' perceptions reflected positive perceptions toward blended learning models. Students believe that the implementation of the blended learning model in learning English is beneficial during the new normal era. Students experience the benefits of learning English using a blended learning model, both online and face-to-face. Based on these results, this study provides an evaluation of the implementation of a learning model in the 21st century, especially during the COVID-19 pandemic crisis, such as using a blended learning model in the process of teaching and learning English in high schools. In conclusion, the majority of students at Senior High School 1 Harau revealed positive perceptions of English blended learning during the new normal era.